Cannabis, alcohol use, psychological distress, and decision-making style. Issue 7 (9th August 2017) - Phillips, James G.; Ogeil, Rowan P.
ABSTRACT: Introduction : There have been suggestions of hypofrontality in cannabis users. To understand cannabis-related differences in decisional processes, Janis and Mann's conflict model of decision making was applied to recreational cannabis smokers who varied in their alcohol use and level of psychological distress. Method : An online sample of recreational substance users (114 male, 119 female) completed the Melbourne Decision Making Questionnaire, the Alcohol Use Disorders Identification Test (AUDIT), Kessler's Psychological Distress Scale (K10), and the Severity of Dependence Scale (SDS) for cannabis. Results : Multivariate analysis of variance examined self-reported decision-making styles as a function of gender, recent cannabis use, risky alcohol consumption, and levels of psychological distress. Psychological distress was associated with lower decisional self-esteem and higher levels of procrastination and buck-passing. There were gender differences associated with cannabis use. Female cannabis users reported higher levels of hypervigilance, while male cannabis users reported lower levels of buck-passing. Conclusions : Although there was little indication of an avoidant decisional style in cannabis users, the results suggest that cannabis affects decisional processes, contributing to panic in females and impulsivity in males.